Implikasi SEMA No. 2 Tahun 2023 terhadap Disparitas Cultus dalam Perspektif Undang-Undang Perkawinan dan Hukum Gereja Katolik - Letsoin, Yetva Softiming; Blareq, Yoseph Koverino Gedu; Sembiring, Kristinus (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
This paper focuses on an elaboration of the implications of SEMA No. 2 of 2023 for interfaith marriages/ Disparitas Cultus in Indonesia. The implications are raised from a discussion with the Republic of Indonesia Law on Marriage and the perspective of Catholic Church Law as seen in the Code of Canon Law. The methodology used is descriptive qualitative and critical reading of the text, namely: The Code of Canon Law that regulates Disparitas Cultus (especially Canon 1086, Canon 1125, Canon 1126, and other related canons) and Law Number 1 of 1974 article 2 paragraph (1) juncto article 66; and other related laws. The author finds that SEMA No. 2 Year 2023 raises quite complex issues. The complexity lies in the consequences. First, the state more explicitly does not recognize Disparitas Cultus marriages. Second, the state is not present to accommodate the interests of people who enter into Cult Disparity marriages. Third, there is a question of justice for those who continue to enter into these marriages. Fourth, the strong and fair foundation or motive of a legal decision is not raised.